Walking activity after multilevel orthopedic surgery in children with cerebral palsy. (26th March 2022) - Church, Chris; Biermann, Isabel; Lennon, Nancy; Henley, John D.; Butler, Stephanie; Niiler, Tim; Shrader, Michael Wade; Miller, Freeman; Howard, Jason J.
Abstract : Aim: To determine how surgical burden and preoperative factors affect the recovery of walking activity after multilevel orthopedic surgery (MLS). Method: In this retrospective study, inclusion criteria were a diagnosis of cerebral palsy, MLS, and walking activity monitoring using a StepWatch device within 12 months pre‐MLS and 24 months post‐MLS. The outcome measure was total mean strides per day normalized to age and Gross Motor Function Classification System level. Pre‐ and postoperative walking activity were compared using unpaired t‐ tests; the effects of preoperative predictors and surgical burden on the recovery of walking activity were evaluated using regression analysis. Results: Participants included 178 children (mean age 12 years 10 months [SD 8 years 7 months; range 4–20 years]; 91 males, 87 females). On average, children returned to baseline walking activity 3 months after low‐burden surgery and 1 year 2 months after high‐burden surgery. Postoperative walking activity was higher for children who had surgery at a younger age and those with a higher preoperative mobility function. Interpretation: The burden of MLS was found to be inversely related to the time to recovery of postoperative walking activity. These findings provide evidence to help clinicians set expectations for return to function post‐MLS. Further study is necessary to investigate the impact of postoperative factors on walking activity recovery. What this paper adds: High‐burden surgeries lead to longer recovery than low‐burden surgeries. Younger children recover walking activity faster after multilevel orthopedic surgery. Children with high preoperative mobility function recover walking activity faster after surgery. What this paper adds: High‐burden surgeries lead to longer recovery than low‐burden surgeries. Younger children recover walking activity faster after multilevel orthopedic surgery. Children with high preoperative mobility function recover walking activity faster after surgery. This article's abstract has been translated into Portuguese. Follow the links from the abstract to view the translations. podcast: https://youtu.be/qw8Sorp6928 ResumoAtividade de caminhada após cirurgia ortopédica multinível em crianças com paralisia cerebral: Objetivo: Determinar como a carga cirúrgica e os fatores pré‐operatórios afetam a recuperação da atividade de caminhada após cirurgia ortopédica multinível (MLS). Métodos: Neste estudo retrospectivo, os critérios de inclusão foram um diagnóstico de paralisia cerebral, MLS e monitoramento da atividade de caminhada usando um dispositivo Step Watch dentro de 12 meses pré‐MLS e 24 meses pós‐MLS. A medida de resultado foi o total de passos médios por dia normalizados para idade e nível do Sistema de Classificação da Função Motora Grossa. A atividade de caminhada pré e pós‐operatória foi comparada usando testes t não pareados; os efeitos dos preditores pré‐operatórios e da carga cirúrgica na recuperação da atividade de caminhada foram avaliados por meio de análise de regressão. Resultados: Os participantes incluíram 178 crianças (idade média de 12 anos e 10 meses [DP 8 anos e 7 meses; intervalo de 4 a 20 anos]; 91 meninos, 87 meninas). Em média, as crianças retornaram à atividade de caminhada inicial 3 meses após a cirurgia de baixa carga e 1 ano e 2 meses após a cirurgia de alta carga. A atividade de caminhada pós‐operatória foi maior para crianças que foram operadas em idade mais jovem e aquelas com maior função de mobilidade pré‐operatória. Interpretação: A carga de MLS foi inversamente relacionada ao tempo de recuperação da atividade de caminhada pós‐operatória. Esses achados fornecem evidências objetivas para ajudar os médicos a definir as expectativas de retorno à função pós‐MLS. Mais estudos são necessários para investigar o impacto dos fatores pós‐operatórios na recuperação da atividade de caminhada.